Evaluation of Contraindication of Thrombolytic Therapy and Its Causes after AMI in Hamadan Ekbatan Hospital in 2002 - Shahram Homayonfar (پزشکی بالینی ابن سینا, 2005)
Acute myocardial infarction (AMI ) is one of the most common cause of mortality in almost all countries of the world. According to this fact that thrombus formation and coronary obstruction are the basic pathophysiology of AMI , early thrombolysis and reperfusion of coronary artery have important role in the reduction of mortality rate and it’s complications. So , recognition of the preventive causes of thrombolytic therapy is very important.